Finite element model updating of masonry minarets by using operational modal analysis method - Calayir, Yusuf; Yetkin, Musa; Erkek, Hakan (Elsevier Science Inc, 2021)
In this paper, finite element model (FEM) updating of masonry minarets was conducted by using dynamic characteristics obtained from Operational Modal Analysis (OMA). For numerical application, Mustafa Sahin mosque minaret in Turkey's Elazig province was selected. In the finite element modelling, structure-foundationsoil interaction was considered. Soil, foundation and structure domains were assumed to be linearly elastic. The masses of foundation and soil were ignored. The FEM updating was performed by comparing the frequencies and mode shapes obtained from the FEM solutions with those of the experimental (OMA) method. The compatibility of numerical and experimental modes was controlled by the Modal Assurance Criterion (MAC) values. The FEM solutions were obtained by using ANSYS finite element package program.
Keywords: Finite element model updating; Dynamic characteristics; Operational modal analysis; Masonry minaret